EKSPLORASI JAMUR ENTOMOPATOGEN DARI TANAH DATARAN RENDAH DENGAN INSECT BAIT METHOD UNTUK MENGENDALIKAN HAMA Spodoptera frugiperda JE. Smith (Lepidoptera:Noctuidae) - Anu Watu, Getrud Novia; Sudiarta, I Putu; Darmiati, Ni Nengah; Yuliadhi, Ketut Ayu; Singarsa, I Dewa Putu; Gargita, I Wayan Diksa (Agriculture Faculty of Flores University, 2025)
Corn (Zea mays L.) is one of the leading food commodities in Indonesia whose availability is often not optimally met. The decline in productivity in agricultural land caused by pest attacks is a very damaging and detrimental factor. Biological control using biological agents in the form of entomopathogenic fungi is an alternative choice for controlling corn pests that is quite cheap but environmentally friendly so as to maintain the balance of the environmental agro-ecosystem. The purpose of this research is to identify the types of entomopathogenic fungi from exploration using the insect bait method in several lowland soil samples that have great potential as biological agents to control Spodoptera frugiperda pests that attack corn plants. The results of the study showed that the lowland soil samples of Tojan, Klungkung and Saba, Blahbatuh, Gianyar did not find symptoms of entomopathogenic fungi that infect the insect pest S. Frugiperda, while the lowland soil samples of Padanggalak, Sanur found symptoms of entomopathogenic fungi that infect the insect pest S. Frugiperda. The results of the pathogenicity test and macroscopic and microscopic identification showed that the characteristics of the isolates refer to the fungus Aspergillus flavus.